The art of the dogon ([New York?] Home Vision, 1988)
Attempts to capture the beauty and power of Dogon Art while placing it in context with Dogon beliefs and culture.
VHS format.
Produced and directed by John Goberman, Marc Bauman in conjunction with an exhibition from the collection of Lester Wunderman.
Sue Cott, narrator.
Keywords: Wunderman, Lester -- Art collections -- Exhibitions; Art, Dogon -- Exhibitions; Art, primitive -- Mali -- Exhibitions; Art, African; Africa, West -- Civilization